1977
DOI: 10.1203/00006450-197703000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Rabbit Alveolar Macrophage during Animal Development. I. Perinatal Influx into Alveoli and Ultrastructural Differentiation

Abstract: hlultiple c r p t a l cru\s-scctlon;il cclioc;trtlic~graphy ill the tli;ignosis o f cy-:111olic corigcrlit:~I l~c ;~r t disca\e. C'ircc~I;it~,~i~. 50: 230 (1074).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 0 publications
4
54
0
Order By: Relevance
“…Our laboratory has previously found that spontaneous MMP-9 secretion by alveolar macrophages in newborn rats significantly varied with the lung growth phase (10). The number of alveolar macrophages is expected to be very low in premature neonates (10,38), as confirmed here, and this may also contribute to the lower MMP-9 levels observed with increasing prematurity. Hyaline membrane disease was associated with increased MMP-9 level in the airways on days 3 and 5 of life; this level correlated with the number of inflammatory cells, suggesting that MMP-9 mainly originated from recruited, activated alveolar macrophages and neutrophils.…”
Section: Discussionsupporting
confidence: 54%
“…Our laboratory has previously found that spontaneous MMP-9 secretion by alveolar macrophages in newborn rats significantly varied with the lung growth phase (10). The number of alveolar macrophages is expected to be very low in premature neonates (10,38), as confirmed here, and this may also contribute to the lower MMP-9 levels observed with increasing prematurity. Hyaline membrane disease was associated with increased MMP-9 level in the airways on days 3 and 5 of life; this level correlated with the number of inflammatory cells, suggesting that MMP-9 mainly originated from recruited, activated alveolar macrophages and neutrophils.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, in rabbits AM are present in BAL samples taken prior to birth and remain the predominate cell type found in lung washings throughout postnatal development (24,25). The cell populations present in pulmonary air spaces of newborn infants are not well defined.…”
Section: Discussionmentioning
confidence: 90%
“…The early postnatal development of AM function has been studied extensively in rabbits (24,25,(28)(29)(30)(31). Using an in vitro assay Sieger (25) found that AM from newborn rabbits were able to kill opsonized bacteria as efficiently as adult AM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical ventilation with intermittent positive airway pressure and high 0, levels might also interfere with the pulmonary defense system and cause a more rapid proliferation of bacteria (43). Nearterm rabbit fetuses born by cesarean section show a decreased capacity to kill invading microorganisms in comparison to animals that are born spontaneously, probably reflecting a delayed influx of phagocytes into the bronchoalveolar space (44). These circumstances might to some extent explain why we, in contrast to other investigators (42), could observe proliferation of GBS in near-term rabbits.…”
Section: Herting Etalmentioning
confidence: 99%